If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + 13 = 39 Reorder the terms: 13 + x = 39 Solving 13 + x = 39 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-13' to each side of the equation. 13 + -13 + x = 39 + -13 Combine like terms: 13 + -13 = 0 0 + x = 39 + -13 x = 39 + -13 Combine like terms: 39 + -13 = 26 x = 26 Simplifying x = 26
| 1/8x=8 | | Ifx-3=16 | | 6x+24=48 | | 40/85 | | 2(4x-4)=8 | | 75/85 | | 1/2+5x=30 | | 2/3+5x=35 | | 2x+12=4x-28 | | 4(-4)-2y= | | 2(x+1)+3(2x-5)=35 | | (5x^4)-2x-4.25=0 | | 4(x+60)+4x=1000 | | 25-7x+3=-3x-11+15x | | 3(-9)+5(-3)+6= | | 7(4)-3(-2x)= | | x^2-9/(x^2)-4 | | 2*0.6*5*5*5= | | 2(0.6)(125)= | | 1/2(4)(-4) | | (5y^2-5y-2)(y^2-5y+5)= | | 16+12-2= | | (12-2)(4+6)= | | -2-9x=-12x+1 | | (4/r^2)+(3/r)=1 | | (9+4-2)*(5-6)= | | 2x-y=3x^2n | | 3x^2-1x-10= | | 4nx=13-2n | | 8x^2-8x-48= | | 9x^2-3x+18= | | (-11+x)(3x-7)= |